Rediscovery of Chaetostomus setosus Boulenger 1887 (Siluriformes, Loricariidae), and assessment of the external characters used for determination of genera within the Chaetostoma group - Provenzano, Francisco R. (Zootaxa, 2018)
During a survey of loricariid catfishes from Colombia, specimens that match the original description of Chaetostomus setosus Boulenger, 1887 were found. This is the first record after the original description. A redescription and a precise capture locality of the species are provided. The analysis of external characters indicate that the species belongs within the Chaetostoma group; however, specimens of C. setosus possess a mixture of external characters that make generic identification difficult. Tentatively, the species is allocated to the genus Cordylancistrus. External morphology of the known species that belong to the Chaetostoma group (mainly type specimens) was analyzed to find diagnostic characters that may be used for appropriate generic assignment. The results of this analysis are presented herein.